2018
DOI: 10.1038/s41598-018-29800-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the maximum serum creatinine value and growth rate in acute paraquat poisoning patients

Abstract: This retrospective and a single-center study evaluated the prognostic value of the maximum serum creatinine value (maxCr) and the maximum serum creatinine growth rate (Vmax) after paraquat (PQ) ingestion. One hundred and seventy-one patients with PQ poisoning were treated with a uniform protocol. Demographic variables, clinical manifestations, relevant laboratory data, maxCr and Vmax of all patients were recorded and calculated. The time after PQ ingestion of maxCr and Vmax were also recorded. Vmax and MaxCr e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
2
11
0
5
Order By: Relevance
“…In the present study, Cox proportional hazard regression analyses indicated that plasma PQ concentration and creatinine were independent risk factors. Our study agrees well with previous studies that elevated plasma PQ concentration [1,26,27] and creatinine [28,29] are significant predictors of mortality in PQ poisoning. To the best of our knowledge, the present study is the first analysis of the association of PLR with outcomes of PQ poisoning, and our study suggests that PLR is not a prognostic predictor for patients with acute PQ intoxication.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, Cox proportional hazard regression analyses indicated that plasma PQ concentration and creatinine were independent risk factors. Our study agrees well with previous studies that elevated plasma PQ concentration [1,26,27] and creatinine [28,29] are significant predictors of mortality in PQ poisoning. To the best of our knowledge, the present study is the first analysis of the association of PLR with outcomes of PQ poisoning, and our study suggests that PLR is not a prognostic predictor for patients with acute PQ intoxication.…”
Section: Discussionsupporting
confidence: 93%
“…All large hospitals have a fever clinic that isolates patients with all kinds of acute communicable diseases as the first line of medical defense. The emergency department, as the second line of medical defense in hospitals, is constantly shouldering the heavy responsibility of screening communicable diseases while also treating all kinds of other non-communicable acute and critical diseases (Zhang et al, 2012;Zhu et al, 2015;Wang et al, 2017;Feng et al, 2018;Lu, 2018;Xu and Lu, 2019). An outbreak of pneumonia of unknown etiology that began in Wuhan city (China) has spread rapidly in China since December 2019 (Huang et al, 2020;WHO, 2020;Zhu et al, 2020).…”
mentioning
confidence: 99%
“…Given that TwHF is a good immunosuppressive agent, its potential anti-inflammatory and immunosuppres-sive mechanisms should be explored to extend its clinical application. Paraquat poisoning-induced acute lung injury is thought to be associated with a strong and persistent inflammatory response Feng et al, 2018;Xu and Lu, 2019). Our group has reported that an acquired immune deficiency syndrome (AIDS) patient who ingested a lethal dose of paraquat had a good prognosis (Shang and Lu, 2015).…”
Section: Prospects For the Futurementioning
confidence: 99%